MODEL KEBIJAKAN MIX SCANNING DALAM PENGEMBANGAN PARIWISATA CIANJUR SELATAN - Mulyana, Yaya; Huraerah, Abu; Martiawan, Rudi (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2019)
Tourism has grown spectacularly as a mainstay sector in various countries in gaining foreign exchange and economic growth, including Indonesia. Likewise, for one of the regions in Indonesia, Cianjur Regency which has a variety of interesting tourist attractions and many are visited by tourists such as Cipanas. Tourism in Cianjur Regency not only in North Cianjur but also in South Cianjur has very potential tourism potential. But unfortunately the management is not optimal so that its potential has not been explored. Therefore, this study will examine the extent to which a tourism policy formulation model that is incremental, elitist and rational comprehensively feels towards the mix scanning model in developing South Cianjur tourism. This study uses descriptive analysis method to explore the object being studied. The type of data used is data in the form of interviews, secondary. The results of the study show that the formulation of existing policies has not been able to optimally improve the performance of the tourism sector.Keywords: Policy Formulation Model, Tourism Development and Local Government. DOI : https://doi.org/10.33005/jdg.v9i2.1627